(untitled) (Research, Society and Development, 2020)
The objective of this work was to verify the effect of different soil compaction degree on the development of Ilex paraguariensis. The study was conducted in a greenhouse at UNICENTRO in Guarapuava, PR. For the culture implantation, pots of 0.15 m diameter were made with PVC tubes, subdivided into rings. The upper and lower ring presented thickness of 0.20 m and were subjected to soil compaction degree (GC) of 75%, while the intermediate ring presented thickness of 0.05 m, and received GC of 75, 80, 85, 90 and 95%. It was verified a negative effect of the mate herb growth due to soil compaction, being the soil compaction degree of 85% more favorable for the development of the Ilex paraguariensis.